Does a Diet Rich in the Bacterium Rhodopirellula rubra Improve Daphnia magna Performance? - Maria Marinho; Gustavo Jesus; Luís Spencer; José Catita; Olga M. Lage; Sara C. Antunes (Frontiers in Bioscience-Elite, 2022)
Background: In the wild various organisms contribute to daphnids diet. This study, intendeds to evaluate the potential of the concentration of Rhodopirellula rubra as a single or supplementary food source for Daphnia magna. Methods: Feeding assays were performed according to standard guidelines for chronic assays (21 days), and life-history parameters and several biomarkers (protein content, oxidative stress, energetic reserves and pigments) were measured. Five food regimens were conducted with 20 individual replicates (A - R. subcapitata; 0.2 - suspension of R. rubra at 0.2 arbitrary units (AU); 0.4 - suspension of R. rubra at 0.4 AU; 0.2+A - suspension of R. rubra at 0.2+alga; 0.2+A-suspension of R. rubra at 0.4 AU + alga). Additionally, the effects of three diets (A, 0.2, and 0.2+A) on the longevity of D. magna were assessed. Results: The five diets showed a different C, N, and carotenoids composition, with an increase in the mixed diets. The results confirmed that the mixed diets improved D. magna life-history parameters. A decrease in glycogen, and the increase of haemoglobin, protein, and gluthione-S-transferase (GST) were observed. Furthermore, D. magna fed with bacterial single diets, presented worsen life history parameters and a decrease in the protein content. An induction of oxidative stress response (increased catalase and GST), and a significant decrease in lipid peroxidation and an accumulation of glycogen and carotenoids were observed. Overall, an increase in the amount of R. rubra provided to D. magna, from 0.2 AU to 0.4 AU, negatively impacted daphnid performance. No significant effects on Daphnia longevity (a 110-day assay) were observed among the three diets tested. However, a significant survival percentage and fertility (cumulative offspring is more than twice) was observed when D. magna was fed with the mixed diet. Conclusions: Results demonstrated that different diets provided a nutritional diversified food to the daphnids that induced differences in D. magna performance. The mixed diets proved to be beneficial (with increase in offspring) on D. magna performance, independently of the bacterial concentration tested. When in single diet, bacterial concentration is not nutritionally sufficient to raise D. magna even when in increased concentration.